Clinical and Histopathological Study of Diclofenac SodiumAcetylsalicylic Acid Toxic Effect on Liver of Mice (Indian Journal of Forensic Medicine & Toxicology, 2020)
Both over-the-counter (OTC) and prescription analgesics-antipyretics like ibuprofen which is nonsteroidalanti-inflammatory drugs (NSAIDs) have effective as well as safe use for long time. Reversible inhibitionof cyclooxygenase enzymes is the mode of action of NSAIDs over all. Use of NSAID lead to drug adversereactions such as cardiovascular and gastrointestinal bleeding also effects of renal. Drug–drug interactions(DDIs) within the NSAID and a concomitant medication cause adverse drug reaction to several cases.DDIs have been reported for example, when commonly used medications as well as some antihypertensive,alcohol, aspirin, antidepressants are coadministered with NSAIDs. Dependent on total drug exposure causea continuous risk in that the potential for an ADR due to interactions pharmacologic nature. When assessingADRs potential risk is important to consideration the use of NSAID dose and duration, also the comedicationtype or class administered. The sub acute toxicity were carried out on thirty mice divided to three equallygroups (10 mice in sub group) which were dosed for two weeks daily as follows: group one (control) wasgivin distilled water, the group two was get diclofenac (voltaren) (100mg/kg B.W.) and group three wasgivin diclofenac (voltaren) with aspirin (100mg/kg B.W.) for each together. Clinical signs of toxicity appearas following: abdominal pain, nausea, dizziness, anorexia, ataxia, blueness of the chest area, shortness ofbreath and Paralysis of the posterior limbs and recumbence, finally the death of mouse. Serum liver enzyme(ALT and AST) were elevated in all groups (diclofenac and diclofenac with aspirin) as compare to controlafter two weeks. Considering histopathological studies of liver tissue after two weeks of daily treatment,which showed moderated mononuclear cells infiltration in portal area around blood vessels and bile ductfor voltaren group and fatty vacuoles in the cytoplasm of hepatic cells, single cells necrosis and severeinflammatory cells infiltration in the capsular area for voltaren with aspirin group. We concluded thatdiclofenac and diclofenac with aspirin have toxic effect appear by clinical symptoms and damage to liver,furthermore, don’t administration of more than one NSAID at same time.